HIV-1 infection in early human placenta in vitro: Effects of Tumor Necrosis Factor (TNF-α) and Interleukins IL-1 and IL-6 - Wu, MD, Fei; Zhang, MD, Fan; Ding, Elizabeth; Ding, MD, PhD, Yan (North American Journal of Medicine and Science, 2016)
The placenta plays a pivotal role in the pathogenesis for the vertical transmission of HIV-1 during pregnancy. To understand HIV-1 infection during the first trimester of pregnancy and its association with inflammatory cytokines, we developed an in vitro HIV infection model using the early human placental explant cultures (5.5-7.5 wks). Ba-L, a laboratory-adapted, chemokine receptor CCR5-using strain of HIV-l, was used to infect the explants. DNA-PCR and Southern blot results show that HIV-l is able to infect the early human placenta in a viral load-dependent manner. In situ PCR demonstrated that the majority of HIV-l-infected cells are cytotrophoblast, Hofbauer cells, and with few syncytiotrophoblast. Viral protein p24 and reverse transcriptase (RT) levels return to control levels after 24h viral exposure, indicating a latent HIV-infection in placental explant culture, though the placenta remained positive by in situ PCR. Viral protein p24 and RT increase by approximately three-fold in the culture supernatants when exogenous cytokines tumor necrosis factor-alpha (TNF-α) alone or in combination with interleukin-1-beta (IL-1β) and IL-6 were added to these virus-exposed explants. Taken together, these data support the hypothesis that the early human placenta is susceptible to HIV-l and latent vs. active HIV-l infection in human placenta may be an important factor in determining whether the baby becomes infected. [N A J Med Sci. 2016;9(4):151-160. DOI: 10.7156/najms.2016.0904151] Key Words: HIV-l, virus infection, trophoblast, in situ PCR, human placenta